2020
DOI: 10.5296/ijafr.v10i1.16749
|View full text |Cite
|
Sign up to set email alerts
|

Board Audit Committee Characteristics and Financial Performance of Selected Commercial Banks in Ghana

Abstract: The purpose of the study was to examine the influence of board audit committee characteristics on the financial performance of selected commercial banks in Ghana during the period of 2008 to 2017. The correlational design was employed. The study population was 23 commercial banks licensed under the Bank and Special Deposit Taking Institution Act with audit committee on their board and offices in Ghana as at December 2018. The sample size for the study was 13 commercial banks in Ghana. The lottery method of sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Likewise, Xie et al (2003) reported that small ACs tend to be more participatory, since they are characterized by a higher oversight capacity than larger ACs. Furthermore, Indrawan et al (2018) and Baiden (2020) revealed that a company with a smaller AC size tended to improve income smoothing practices due to lower supervision in the financial reporting process. On the contrary, the larger the AC size, the smaller the practice of income smoothing.…”
Section: Audit Committee Sizementioning
confidence: 99%
“…Likewise, Xie et al (2003) reported that small ACs tend to be more participatory, since they are characterized by a higher oversight capacity than larger ACs. Furthermore, Indrawan et al (2018) and Baiden (2020) revealed that a company with a smaller AC size tended to improve income smoothing practices due to lower supervision in the financial reporting process. On the contrary, the larger the AC size, the smaller the practice of income smoothing.…”
Section: Audit Committee Sizementioning
confidence: 99%
“…Likewise, Xie et al (2003) reported that small ACs tend to be more participatory, since they are characterized by a higher oversight capacity than larger ACs. Furthermore, Indrawan et al (2018) and Baiden (2020) revealed that a company with a smaller AC size tended to improved income smoothing practices due to lower supervision in the financial reporting process.…”
Section: Audit Committee Sizementioning
confidence: 99%